Mechanically Assisted Total Cavopulmonary Connection With an Axial Flow Pump: Computational and In Vivo Study. Issue 1 (14th December 2015) - Gandolfo, Fabrizio; Brancaccio, Gianluca; Donatiello, Salvatore; Filippelli, Sergio; Perri, Gianluigi; Iannace, Enrico; D'Amario, Domenico; Testa, Giuseppina; D'Avenio, Giuseppe; Grigioni, Mauro; Amodeo, Antonio
Abstract: A relevant number of patients undergoing total cavopulmonary connection (TCPC) experience heart failure (HF). Heart transplant is then the final option when all other treatments fail. The axial flow blood pumps are now the state of the art; however, there is little experience in low‐pressure circuits, such as support of the right ventricle or even a TCPC circulation. A new T‐shaped model of mechanically assisted TCPC using the "Jarvik Child 2000" axial pump, (flow rates between 1 and 3 L/m in a range of 5000–9000 rpm) was designed, simulated numerically, and then tested in animals. Eight sheep (42–45 kg) were studied: two pilot studies, four pump‐supported (PS) TCPC for 3 h, and two not pump‐supported (NPS) TCPC. In the PS, the axial pump was set to maintain the baseline cardiac output (CO). Pressures, CO, systemic and pulmonary vascular resistance, lactate levels, and blood gases were recorded for 3 h. Computational fluid dynamics (CFD) study allows us to set the feasible operating condition and the safety margins to minimize the venous collapse risk. In the NPS animals, a circulatory deterioration, with increasing lactate level, occurred rapidly. In the PS animals, there was a stable cardiac index of 2.7 ± 1.4 L/min/m 2, central venous pressure of 12.3 ± 1 mm Hg, and a mean pulmonary artery pressure (PAP) of 18.1 ± 6 after 3 h of support up to 9000 rpm. systemic vascular resistance (SVR), pulmonary vascular resistance (PVR), blood gasses, and arterial lactate levels remained stable to baseline values. No caval collapse occurred. A new pediatric axial flow pump provides normal CO and physiologic stability in a new T‐shaped model of TCPC in sheep, in vivo. CFD and in vivo data showed that this experimental arrangement will allow us to evaluate the potential for mechanical support in patients with Fontan failure avoiding major adverse events.